Mentoring digital media projects : project-based learning and teaching for professional development - Pennefather, Patrick Parra (Apress, 2023)
Mentoring is often a crucial, yet informal part of an organization's best practices and skill development, whether targeted towards a team lead, project manager, designer, developer or a valued senior team member. This book provides practical strategies and methodologies for professionals to mentor others to successfully develop and deliver digital media projects across different types of settings.Many professionals working with teams in the digital media industry (games, web development, XR, IoT, mobile) are drawn to teaching others, but may not know how or where to start. Many might be a subject expert but may not have the structure and skills in place to be able to teach others effectively in workplace and institutional settings. This handbook will give professionals a guide on how to mentor junior designers, developers and other learners in formal and informal learning environments. Mentoring Digital Media Projects offers the right tools and strategies to use in digital media and emerging tech projects for you to better guide junior team members What You'll Learn Understand the difference between mentoring and teaching Design thinking strategies to better identify where, when and how you can help and mentor others Build mentoring pipelines, end-to end, especially in post-secondary learning environments Create emerging technology projects with teams Who This Book Is For Digital media professionals (game, web development, XR, mobile, IoT, etc.) who have experience working in teams in their specific discipline and who want to mentor others.